2010
DOI: 10.1111/j.1601-0825.2010.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of two novel susceptibility loci for non‐syndromic orofacial clefts in a Chinese population

Abstract: Our findings are consistent with a lack of involvement of the rs7078160 and rs223371 polymorphisms in the development of NSOC in the Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…In accordance with our study, Mangold et al [2010] have found strong evidence of association with NOG rs227731 in a GWAS of a large number of participants from a European population. In contrast, Pan et al [2011] showed genotypes at NOG rs227731 were not associated with risk of NSCLP in the Southern Chinese population. The reason for the discrepancy between the results of our study and those in Pan et al [2011] is unknown, but it unlikely reflects the sample size, since both studies were of similar sample size (188 cases and 228 controls in the current study vs. 199 cases and 210 controls).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In accordance with our study, Mangold et al [2010] have found strong evidence of association with NOG rs227731 in a GWAS of a large number of participants from a European population. In contrast, Pan et al [2011] showed genotypes at NOG rs227731 were not associated with risk of NSCLP in the Southern Chinese population. The reason for the discrepancy between the results of our study and those in Pan et al [2011] is unknown, but it unlikely reflects the sample size, since both studies were of similar sample size (188 cases and 228 controls in the current study vs. 199 cases and 210 controls).…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, Pan et al [2011] showed genotypes at NOG rs227731 were not associated with risk of NSCLP in the Southern Chinese population. The reason for the discrepancy between the results of our study and those in Pan et al [2011] is unknown, but it unlikely reflects the sample size, since both studies were of similar sample size (188 cases and 228 controls in the current study vs. 199 cases and 210 controls). The minor allele frequency for NOG rs227731 in our control was similar to those observed in the Southern Chinese population (0.34 vs. 0.34).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…SNP rs7078160 is intergenic, located near the VAX1 gene encoding a transcriptional regulator with a DNA-binding homeobox domain. An association between rs7078160 and nsCL/P has been replicated in several studies, which included European and Mesoamerican samples 20,21,37 , but Chinese and Kenyan studies 33,34 have reported contradictory results. A meta-analysis of 7 eligible studies 38 showed only a modest association of rs7078160 with nsCL/P risk.…”
Section: Discussionmentioning
confidence: 82%
“…However, the subsequent replication studies conducted in the Mesoamerican, Italian, Chinese Han and Kenyan populations did not confirm these positive results 21,31,33,34 . The nucleotide variant rs227731 is located 100kb centromeric of the NOG gene.…”
Section: Discussionmentioning
confidence: 88%